Sentencing and punishment : the quest for justice - Easton, Susan M.; Piper, Christine (Oxford : Oxford University Press, 2023)
Examining the theory behind the headlines and engaging with current debates, this new edition provides thoughtful, impartial, and unbiased coverage of sentencing and punishment in the UK. Collectively, Susan Easton and Christine Piper are highly experienced teachers and researchers in this field, making them perfectly placed to deliver this lively account of a highly dynamic subject area. The book takes a thorough and systematic approach to sentencing and punishment, examining key topics from legal, philosophical, and practical perspectives. Offering in-depth and detailed coverage, while remaining clear and succinct, the authors deliver a balanced approach to the subject. Chapter summaries, discussion questions, and case studies help students to engage with the subject, apply their knowledge, and reflect upon debates.
This edition also issued in print: 2022.
Previous edition: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 2, 2023).
Keywords: Sentences (Criminal procedure) -- England; Sentences (Criminal procedure) -- Wales; Justice; Punishment; Law; Laws of specific jurisdictions & specific areas of law